Enhancing Students’ Learning Outcomes in Chemistry through Problem-Based Learning: A Systematic Literature Review Supporting Sustainable Development Goal 4 (Quality Education) - Laila, Elva; Festiyed; Yerimadesi; Yulkifli; Diliarosta, Skunda (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to systematically analyze the effectiveness of Problem-Based Learning (PBL) in enhancing students’ learning outcomes in chemistry education. This research employed a Systematic Literature Review (SLR) approach following PRISMA 2020 guidelines with strict inclusion criteria. A total of 30 empirical studies published between 2010 and 2025 were selected from Scopus- and SINTA-indexed journals. The findings indicate that PBL significantly improves students’ conceptual understanding, critical thinking, and problem-solving skills, particularly in topics such as reaction rates, chemical equilibrium, and acid–base chemistry. Furthermore, the integration of PBL with digital media and contextual approaches strengthens its effectiveness in supporting meaningful learning. However, challenges related to teacher readiness and the need for appropriate scaffolding remain critical issues. This study contributes to the achievement of Sustainable Development Goal 4 (Quality Education) by promoting effective student-centered learning strategies in chemistry education.